Synthesis of hypercrosslinked poly(acrylonitrile-co-ethylene glycol dimethacrylate-co-vinylbenzyl chloride) as adsorbent for pharmaceuticals - Shaipulizan, Nur Syafiqah (2020)
Pharmaceuticals are frequently present in water at concentrations in the μg.L-1 to ng.L-1 range and this range is considered to be a possible threat to the environment. The presence of pharmaceuticals caused sexual disruption in wild fish and harmful to the aquatics. The present work describes the preparation of porous polymeric adsorbent to adsorb pharmaceuticals from water. Ethylene glycol dimethacrylate (EGDMA) was used as a crosslinker in poly(acrylonitrile (AN)-co-vinylbenzyl chloride (VBC)) to investigate the effect of long-chain crosslinker to the porosity of the terpolymer system. Poly(acrylonitrile-co-ethylene glycol dimethacrylate-co-vinylbenzyl chloride) (poly(AN-co-EGDMA-co-VBC)) with different feed mole ratios of AN and EGDMA were synthesized via suspension polymerization method and further hypercrosslinked by Friedel-Crafts reaction. The performance of the terpolymeric adsorbent to adsorb polar analyte is evaluated by adsorbing each of the pharmaceuticals, metformin (MET) and diclofenac (DCF) from aqueous solution at different conditions in a batch system. The isotherm and kinetic studies were carried out by using batch adsorption data. The ratio of AN/EGDMA/VBC were varied to 20/70/10, 25/65/10 and 30/60/10 (mol%). Poly(AN-co-EGDMA-co-VBC) 20/70/10 obtained the highest percentage yield (86%) compared to the other terpolymers. The FT-IR spectra confirmed the successful of polymerization due to the appearance of absorption bands of C≡N, C=O, C-O-C and CCl groups in the spectra of all ratios of terpolymers. The absorption band at 1251 cm-1 that was assigned to the C-Cl vibrations was less intense in all hypercrosslinked (HXL) poly(AN-co-EGDMA-co-VBC) polymers, confirming that the hypercrosslinking reaction was successful. The microanalysis showed the increasing of carbon, hydrogen and oxygen contents with the decreasing of nitrogen content of the terpolymers as the mole ratios of EGDMA increased. The Field Emission Scanning Electron Microscopy (FESEM) micrographs showed that poly(AN-co-EGDMA-co-VBC) and HXL poly(ANco- EGDMA-co-VBC) have spherical particle structures. Based on the EDX analysis, the chlorine content of polymers decreased after the hypercrosslinking reaction indicating that the chloromethyl groups were being consumed during hypercrosslinking reaction. Poly(AN-co-EGDMA-co-VBC) 20/70/10 showed the highest specific surface area (363 m2.g-1), micropore area (33 m2.g-1), total pore volume (0.482 cm3.g-1) and micropore volume (0.025 cm3.g-1). Broad mesopores range from 2–10 nm are the main pores for all terpolymers to indicate that mesopores are dominant for the polymers. Pore size distribution (PSD) estimated by Barrett-Joyner-Halenda (BJH) method revealed that all terpolymers are centred at around 5–8 nm, which confirmed that terpolymers prepared in this study are mesoporous materials. The Langmuir isotherm showed good agreement for the adsorption of MET (R2 of 0.9637) and DCF (R2 of 0.9689) with maximum adsorption capacities of 5.1 mg.g-1 and 61.0 mg.g-1, respectively. The pseudo-second-order was observed to have better R2 compared to the other models for both MET and DCF. After four cycles of adsorption-desorption process, DCF and MET removal decreased from 99% to 78% and 76% to 72%, respectively. Based on experimental findings, HXL poly(AN-co- EGDMA-co-VBC) polymer is a potential functional regenerable adsorbent to remove pharmaceuticals from liquid environment.